2015
DOI: 10.1007/s00726-015-2081-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and microassay of a nitrite-dependent carbonic anhydrase activity by stable-isotope dilution gas chromatography–mass spectrometry

Abstract: The intrinsic activity of carbonic anhydrase (CA) is the hydration of CO2 to carbonic acid and its dehydration to CO2. CA may also function as esterase and phosphatase. Recently, we demonstrated that renal CA is mainly responsible for the reabsorption of nitrite (NO2(-)) which is the most abundant reservoir of the biologically highly potent nitric oxide (NO). By means of a stable-isotope dilution GC-MS method, we discovered a novel CA activity which strictly depends upon nitrite. We found that bovine erythrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Nitrate is able to bind to carbonic anhydrase active site [ 104 ], but not it cannot be utilized to form S-nitrosothiols as nitrite can be [ 105 ]. It can inhibit platelet aggregation in whole blood, but the mechanism remains unclear [ 101 ].…”
Section: Platelet Carbonic Anhydrasementioning
confidence: 99%
“…Nitrate is able to bind to carbonic anhydrase active site [ 104 ], but not it cannot be utilized to form S-nitrosothiols as nitrite can be [ 105 ]. It can inhibit platelet aggregation in whole blood, but the mechanism remains unclear [ 101 ].…”
Section: Platelet Carbonic Anhydrasementioning
confidence: 99%
“…As CA inhibitors may have unknown off‐target effects due to different tissue specific isozymes expression (Swenson, 2016), the CAII deficient mouse model allowed us to characterize the function of CAII in nitrite signalling, on a relatively clean background. Although renal carbonic anhydrases (CAII and CAIV) are involved in the reabsorption of endogenous nitrite (Chobanyan‐Jürgens et al, 2012; Zinke et al, 2016), we examined the effect of CAII KO on endogenous nitrite levels in urine and no differences were detected among CAII −/− , CAII +/− , and wild‐type mice. Our assessment of levels of plasma nitrite support this finding with similar nitrite levels across the genotypes (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Haemoglobin (Basu et al, 2007), nitrophorin (He & Knipp, 2009), and the zinc‐containing carbonic anhydrase (CA) II (Aamand et al, 2009b) have been reported to exhibit nitrite anhydrase activities. However, the role of CAII in nitrite‐dependent NO formation remains controversial as a number of studies have been unable to detect changes in measured NO formation from nitrite with red blood cells (Liu et al, 2015) and in vivo after treatment with CA inhibitors (Andring et al, 2018; Pickerodt et al, 2018; Zinke, Hanff, Böhmer, Supuran, & Tsikas, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of endogenous CysSNO is unclear. CysSNO can be formed from CysSH and higher oxides of NO including nitrous acid (HONO) and its anhydride (N 2 O 3 ) [28] , [29] .…”
Section: Introduction Of No and S -Nitrosothiolsmentioning
confidence: 99%